Development of an integrative learning program for community dwelling old people with dementia - Thomas Kwok Shing Wong; Yang Yunhua; Chen Jinghan; Carmen Ka Man Lee; Zhou Ying; Jiang Liping; Tang Qiubi; Joanne Wai Yee Chung (Universidade de São Paulo, 2021)
Objective: to develop an integrative learning program for people with dementia. Method: a methodological study was conducted using Delphi technique to develop the learning program, followed by a feasibility test. An expert panel was invited to develop the integrative learning program based on the neuroplasticity and learning framework. A feasibility test was conducted to evaluate the implementation of the program in two centers after the training of personnel who run the program. Verbatim transcripts of case conferences were coded, analyzed, and collapsed into themes and sub-themes by consensus. Results: there was no indication for content modification during the period of program implementation. Qualitatively, the participating older adults showed improvement in communications, emotions, connectedness with self and others, and well-being. Conclusion: the integrative learning program was uneventfully implemented with promising results. The program is ready for full-scale research on its efficacy in multiple centers to obtain more robust evidence.